2020
DOI: 10.3389/fendo.2020.00103
|View full text |Cite
|
Sign up to set email alerts
|

The Atypical Cannabinoid Abn-CBD Reduces Inflammation and Protects Liver, Pancreas, and Adipose Tissue in a Mouse Model of Prediabetes and Non-alcoholic Fatty Liver Disease

Abstract: Results: Body weight and triglycerides profiles in blood and liver were comparable between vehicle-and Abn-CBD-treated DIO mice. However, treatment with Abn-CBD reduced hyperinsulinemia and markers of systemic low-grade inflammation in plasma and fat, also promoting white adipose tissue browning. Pancreatic islets from Abn-CBD-treated mice showed lower apoptosis, inflammation and oxidative stress than vehicle-treated DIO mice, and beta cell proliferation was induced. Furthermore, Abn-CBD lowered hepatic fibros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 51 publications
(65 reference statements)
5
19
0
2
Order By: Relevance
“…Abn-CBD significantly reduced beta cell apoptosis in both T1D mouse models, in agreement with previous reports in mouse models of type 2 diabetes (Ruz-Maldonado et al, 2018;Vong et al, 2019b;Romero-Zerbo et al, 2020), in which Abn-CBD was shown to reduce cytokine (mix of TNFα, IFNγ and IL-1β)-induced apoptosis in islets in vitro (Ruz-Maldonado et al, 2018). IL-6, which is elevated in T1D (Alnek et al, 2015), plays a very important role at the onset of T1D by activating CD4 + T cell differentiation (Hundhausen et al, 2016).…”
Section: Discussion and Concusionssupporting
confidence: 91%
See 3 more Smart Citations
“…Abn-CBD significantly reduced beta cell apoptosis in both T1D mouse models, in agreement with previous reports in mouse models of type 2 diabetes (Ruz-Maldonado et al, 2018;Vong et al, 2019b;Romero-Zerbo et al, 2020), in which Abn-CBD was shown to reduce cytokine (mix of TNFα, IFNγ and IL-1β)-induced apoptosis in islets in vitro (Ruz-Maldonado et al, 2018). IL-6, which is elevated in T1D (Alnek et al, 2015), plays a very important role at the onset of T1D by activating CD4 + T cell differentiation (Hundhausen et al, 2016).…”
Section: Discussion and Concusionssupporting
confidence: 91%
“…We did not find a significant increase in beta cell proliferation in Abn-CBD-treated STZ-induced diabetic mice as compared to vehicle-treated mice that may account for the lack of improved glycemia over the short experimental period time. These results challenge previous reports indicating that Abn-CBD stimulated beta cell proliferation in the STZ-treated Swiss mouse model as well as in a diet-induced mouse model of obesity and prediabetes and isolated human islets (McKillop et al, 2016;Ruz-Maldonado et al, 2018;Romero-Zerbo et al, 2020). Discrepancies may potentially be related to differences in time and via of administration.…”
Section: Discussion and Concusionssupporting
confidence: 63%
See 2 more Smart Citations
“…Cannabinoids, the chemical compounds found in the cannabis (marijuana) plant, exhibit pharmacobiological effects in various conditions, including remyelination [ 1 ], hyperthermia [ 2 ], hypothermia [ 3 ], catalepsy [ 4 , 5 ], inflammation and immune activation [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ], analgesia [ 13 ], cellular growth/arrest, apoptosis [ 14 ], as well as alteration in the functions of a variety of immune cells [ 15 , 16 , 17 , 18 ]. Although more than 100 cannabinoids have been identified in cannabis, THC and the non-psychotropic cannabidiol (CBD) are the most widely used and both have the same molecular formula (C 21 H 30 O 2 ) and molecular weight (314.5 g/mol).…”
Section: Introductionmentioning
confidence: 99%